Do Financial Incentives Influence GPs' Decisions to Do After‐hours Work? A Discrete Choice Labour Supply Model. (20th February 2017) - Broadway, Barbara; Kalb, Guyonne; Li, Jinhu; Scott, Anthony
Abstract: This paper analyses doctors' supply of after‐hours care (AHC), and how it is affected by personal and family circumstances as well as the earnings structure. We use detailed survey data from a large sample of Australian General Practitioners (GPs) to estimate a structural, discrete choice model of labour supply and AHC. This allows us to jointly model GPs' decisions on the number of daytime‐weekday working hours and the probability of providing AHC. We simulate GPs' labour supply responses to an increase in hourly earnings, both in a daytime‐weekday setting and for AHC. GPs increase their daytime‐weekday working hours if their hourly earnings in this setting increase, but only to a very small extent. GPs are somewhat more likely to provide AHC if their hourly earnings in that setting increase, but again, the effect is very small and only evident in some subgroups. Moreover, higher earnings in weekday‐daytime practice reduce the probability of providing AHC, particularly for men. Increasing GPs' earnings appears to be at best relatively ineffective in encouraging increased provision of AHC and may even prove harmful if incentives are not well targeted. Copyright © 2017 John Wiley & Sons, Ltd.